Psychedelic therapy: bridging neuroplasticity, phenomenology, and clinical outcomes - Kishon, Ronit; Cycowicz, Yael M. (Frontiers in Psychiatry, 2025)
The resurgence of interest in psychedelic compounds as potential treatments for psychiatric disorders represents a paradigm shift in mental health care. Psychedelics exert their effects through serotonergic modulation, particularly via 5-HT2A receptor activation, inducing profound alterations in consciousness and catalyzing neuroplasticity. While their neurobiological effects are well-documented, the therapeutic potential of psychedelics extends beyond their biochemical properties. Psychedelic therapy provides a structured framework for integrating the psychedelic experiences, comprising three key phases: preparation, administration, and integration. While current clinical trials focus primarily on establishing pharmacological efficacy across diagnostic categories, the phenomenology of psychedelic experiences offers valuable insights into precision psychiatry. Emerging evidence suggests that therapeutic benefits arise not only from acute symptom relief but also from enduring changes in self-perception, emotion regulation, and interpersonal connectedness. This paper explores the psychological dimensions of psychedelic therapy, emphasizing its implications for psychiatric treatment. By integrating neuroscientific findings with phenomenological insights, we argue that psychedelics represent more than a novel pharmacological intervention. They offer a fundamentally different therapeutic model that necessitates a reconceptualization of mental health treatment. Further research is required to refine treatment protocols, elucidate the relationship between subjective experiences and therapeutic outcomes, and establish best practices for integrating psychedelics into clinical settings.